Body weight lower limits of fetal postmortem MRI at 1.5 T. (8th June 2016) - Jawad, N.; Sebire, N. J.; Wade, A.; Taylor, A. M.; Chitty, L. S.; Arthurs, O. J.
Abstract: Objective: To evaluate the diagnostic yield of postmortem magnetic resonance imaging (PM‐MRI) compared with conventional autopsy in fetuses of early gestational age and low body weight. Methods: Fetuses of < 31 weeks' gestation that underwent 1.5‐T PM‐MRI and conventional autopsy were included. The findings of PM‐MRI and conventional autopsy were reported blinded to each other. The reports of conventional autopsy and PM‐MRI for each organ system (cardiovascular, neurological, abdominal, non‐cardiac thoracic and musculoskeletal) were classified as either diagnostic or non‐diagnostic. The likelihood of a non‐diagnostic examination by PM‐MRI was calculated according to fetal gestational age and body weight. Results: Full datasets were examined of 204 fetuses, with mean gestational age of 20.95 ± 3.82 weeks (range, 12.0–30.7 weeks) and body‐weight range of 15.9–1872 g. Body weight was the most significant predictor of diagnostic yield of PM‐MRI. There was 95% confidence that 90% of fetuses will show diagnostic images by PM‐MRI for all five organ systems when fetal body weight is ≥ 535 g, but < 50% of fetuses will have all five systems diagnostic on PM‐MRI when body weight is < 122 g. Conclusion: PM‐MRI is highly likely to provide adequate diagnostic images for fetuses with a body weight > 500 g. Below this weight, the diagnostic yield of standard 1.5‐T PM‐MRI decreases significantly. These data should help inform parents and clinicians on the suitability of performing PM‐MRI in fetuses with low body weight. Copyright © 2015 ISUOG. Published by John Wiley & Sons Ltd.